2019
DOI: 10.2478/fon-2019-0040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abdominal massage on gastrointestinal function in ICU patients: a meta-analysis

Abstract: Objective To evaluate the effects of abdominal massage on gastrointestinal function in the intensive care unit (ICU) patients. Methods Randomized controlled trials about the effects of abdominal massage on gastrointestinal function in ICU patients were included from multiple electronic databases: PubMed, Web of Science, the Cochrane Library, Embase, CINAHL, China Academic Journals Full-Text Database (CNKI), Wanfang Database, and CQVIP, until November 2018. Studies were selected according to inclusion and exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
3
4
0
1
Order By: Relevance
“…This may be attributed to that massage of the abdomen lead to activation of intestine and stomach that cause easy digestion of food, hasting peristalsis, stimulating the nutrients absorption, and facilitating the passage of nutritional components in the intestine, resulting in decreasing abdominal distension (34) . This result was similar with Seiiedi (2020) (35) ,Wang, (2019) (36) and Uysal (2017) (37) who showed that massage of abdomen helps to decrease abdominal circumference, distension, GR, and vomiting. Gastric residual volume is the amount of liquid drained from a stomach following administration of enteral feed.…”
Section: Discussionsupporting
confidence: 85%
“…This may be attributed to that massage of the abdomen lead to activation of intestine and stomach that cause easy digestion of food, hasting peristalsis, stimulating the nutrients absorption, and facilitating the passage of nutritional components in the intestine, resulting in decreasing abdominal distension (34) . This result was similar with Seiiedi (2020) (35) ,Wang, (2019) (36) and Uysal (2017) (37) who showed that massage of abdomen helps to decrease abdominal circumference, distension, GR, and vomiting. Gastric residual volume is the amount of liquid drained from a stomach following administration of enteral feed.…”
Section: Discussionsupporting
confidence: 85%
“…This finding was consistent with the findings of a systematic review and meta-analysis conducted by Xinbo et al [45] , who confirmed that the rate of abdominal distension was significantly lower in the abdominal massage group compared to the control group. Consistent with this finding, Wang et al [46] discovered that abdominal massage decreased the occurrence of gastric residue, abdominal distension, gastric retention, and vomiting among intensive care unit (ICU) patients, demonstrating the massage's efficacy.…”
Section: Discussionmentioning
confidence: 76%
“…Supporting our results, previous studies stated that abdominal massage reduced the incidence of distension. 32,34,35 The meta-analysis study conducted in intensive care units patients by Wang et al 35 stated that significant results were found in the group that was massaged for 7 days compared with the control group.…”
Section: Discussionmentioning
confidence: 99%